A compact cryogenic pump. (April 2016) - Li, Gang; Caldwell, Shane; Clark, Jason A.; Gulick, Sidney; Hecht, Adam; Lascar, Daniel D.; Levand, Tony; Morgan, Graeme; Orford, Rodney; Savard, Guy; Sharma, Kumar S.; Van Schelt, Jonathon
Highlights: A compact centrifugal cryogenic pump for circulating liquid nitrogen has been designed. A novel gas release structure resolved the cavitation problem. The pump has proven reliable and cost-effective for small-scale laboratory use. Abstract: A centrifugal cryogenic pump has been designed at Argonne National Laboratory to circulate liquid nitrogen (LN2 ) in a closed circuit allowing the recovery of excess fluid. The pump can circulate LN2 at rates of 2–10 L/min, into a head of 0.5–3 m. Over four years of laboratory use the pump has proven capable of operating continuously for 50–100 days without maintenance.